Decomposing the linkages between energy consumption, air pollution, climate change, and natural resource depletion in Pakistan. Issue 2 (2nd November 2016) - Zaman, Khalid; Abdullah, Iqra; Ali, Muneeb
Abstract : This study aims at examining the causal relationship between energy consumption, natural resources, environmental pollution (i.e., CO2 emissions) and climate change (i.e., Greenhouse gas emissions ‐ GHG) in the context of Pakistan, over the period of 1975–2012. The study applied bivariate cointegration and Granger causality technique for robust inferences. The results show that energy demand increases gas rents, natural resource rents, and oil rents while it exhausts the natural resources. Natural resources further affected by air pollution and climate change in a country. The results of Granger causality indicate that there is a bidirectional causality between (i) energy consumption and net forest depletion, (ii) energy demand and oil rent, (iii) forest rents and CO2 emissions, (iv) natural resource depletion and GHG emissions, and (v) net forest depletion and GHG emissions, while, there is a unidirectional causality running from CO2 emissions to oil rents, from net forest depletion to CO2 emissions, and from GHG emissions to forest rent, mineral rent, natural gas rent, and oil rent in a country. Finally, the study confirmed the "neutrality hypothesis" between coal rent, natural resource rent, and GHG emissions in Pakistan. © 2016 American Institute of Chemical Engineers Environ Prog, 36: 638–648, 2017